The Relevance of Hadith Principles in Balancing Power within the Legal System of a State - Hardivizon, Hardivizon; Bello, Mufutau Olusola (Institut Agama Islam Negeri Curup, 2023)
In the intricate landscape of constitutional law, the role of Islamic legal principles, particularly those derived from hadith, is gaining prominence in discussions on power balance within a state's legal system. Ensuring a just and effective governance structure necessitates a foundational power balance, preventing concentration within a single entity or institution. This article explores the relevance of hadith principles in shaping a balanced legal order, offering moral and ethical guidance for policy formation, legislation, and governance practices. The research incorporates a critical study of hadith, employing Hassan Hanafi's hermeneutical framework to contextualize hadith within historical and social contexts. By analyzing the ethical values and principles of justice embedded in hadith, the article contributes to understanding the unique role of hadith principles in the dynamics of power within a state's legal system. Through an in-depth examination of relevant studies, the article addresses gaps in existing research, focusing on the specific contribution of hadith principles in establishing a fair and balanced legal foundation. The research methodology involves critical evaluation of hadith authenticity, linguistic analysis, and contextualization, offering a comprehensive understanding of hadith principles' interpretation and application in constitutional law. In conclusion, the article underscores the timeless significance of hadith principles in shaping legal systems that promote accountability, protect citizen rights, ensure transparency, and uphold justice, thereby contributing to a framework for balanced and ethically grounded governance.